Effects of Morphological Age and Indole-3-Butyric Acid Concentration on Rooting of Selected Robusta Coffee Varieties - Kagezi, Godfrey H.; Epedu, Elijah; Bisikwa, Jenipher; Nuwamanya, Ephraim; Ejiet-Igolat, Emmanuel; Manirakiza, Jonath; Magambo, Betty; Arinaitwe, Geofrey (Indonesian Coffee and Cocoa Research Institute, 2025)
In response to the outbreak of Coffee Wilt Disease (CWD) which wiped out almost 50% of Robusta coffee in Uganda, the National Coffee Research Institute (NaCORI) released 10 varieties (KR1-10) which are resistant to the disease. These varieties are being multiplied by stem cuttings for commercialization, although some of them present challenges in rooting. Research shows that rooting ability of stem cuttings is a function of the variety, their morphological status and rooting hormone used, among other factors. We therefore conducted an on-station study to determine the effect of morphological age of the stem cuttings and Indole-3-Butyric Acid (IBA) rooting hormone concentration on the rooting ability of varieties, KR1, KR3 and KR4. A factorial experiment with three stem segments with differing morphological age (softwood, semi-hardwood and hardwood) and five IBA concentrations (0, 1, 2, 4, 7 and 10g/l) was set up for each variety in a completely randomized design and replicated five times. Results showed that the number of roots produced by stem cuttings varied significantly (p?0.05) across varieties and IBA concentration level but not the morphological age of the cuttings. The highest number of roots was recorded on variety KR4, (35.3), 2 g/l of IBA (31.5) and softwood cuttings (29.1). Furthermore, the number of roots produced by stem cuttings varied significantly (P<0.00001) across combinations of factors. The highest number of roots was recorded on softwood treated with 10 g/l of IBA rooting hormone for KR1, hardwood cuttings treated with 2 g/l of IBA for KR3 and softwood cuttings treated with 2 g/l of IBA for KR4. Our findings provide a guide on variety-specific approaches for enhancing rooting ability of stem cuttings of these CWD-r Robusta coffee varieties. We therefore recommend that similar studies be conducted on variety, KR8 which also has been recently reported for challenges of rooting of its stem cuttings.